2006
DOI: 10.1111/j.1365-2699.2006.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical biogeography of South American freshwater fishes

Abstract: Aim  To investigate biogeographical patterns of the obligate freshwater fish order Characiformes. Location  South America. Methods  Parsimony analysis of endemicity, likelihood analysis of congruent geographical distribution, and partition Bremer support were used. Results  Areas of endemism are deduced from parsimony analysis of endemicity, and putative dispersal routes from a separate analysis of discordant patterns of distribution. Main conclusions  Our results demonstrate the occurrence of 11 major areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
244
0
17

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(280 citation statements)
references
References 111 publications
(332 reference statements)
19
244
0
17
Order By: Relevance
“…Ibarra & Stewart, 1989;Galacatos et al, 1996;Stewart et al, 2002;Galacatos et al, 2004). The Upper Amazon (sensu Hubert & Renno, 2006), which includes all rivers west of the Lower Madeira River, is characterized by high endemism and shares few species with other areas of the Amazon basin (Hubert & Renno, 2006). In addition, the Caquetá and Putumayo rivers have a different species composition compared to other rivers within the Upper Amazon (Hubert and Renno, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ibarra & Stewart, 1989;Galacatos et al, 1996;Stewart et al, 2002;Galacatos et al, 2004). The Upper Amazon (sensu Hubert & Renno, 2006), which includes all rivers west of the Lower Madeira River, is characterized by high endemism and shares few species with other areas of the Amazon basin (Hubert & Renno, 2006). In addition, the Caquetá and Putumayo rivers have a different species composition compared to other rivers within the Upper Amazon (Hubert and Renno, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Upper Amazon (sensu Hubert & Renno, 2006), which includes all rivers west of the Lower Madeira River, is characterized by high endemism and shares few species with other areas of the Amazon basin (Hubert & Renno, 2006). In addition, the Caquetá and Putumayo rivers have a different species composition compared to other rivers within the Upper Amazon (Hubert and Renno, 2006). In particular, the ichthyofauna of the Apaporis River, a major tributary of the Caquetá River (about 1200 km long and 47,000 km 2 drainage area) (PAT, 1997), is largely unexplored (Correa, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A "Western Amazonian" area of endemism for fishes has been suggested by other authors (e.g. Kullander, 1986;Reis, 1998b;Wilkinson et al, 2006;Hubert & Renno, 2006) and is here equated to the sedimentary basins situated west of the Purus Arch (see Räsänen et al, 1992: fig. 1), the eastern divide of the Amazon basin prior to the late Miocene (see Lundberg et al, 1998, and references therein).…”
Section: Discussionmentioning
confidence: 93%
“…Because marine incursion events also function as obvious dispersal and ecological barriers, particularly for resident terrestrial and freshwater organisms [9,40], congruent biogeographic patterns would reflect shared responses by different species to the same major vicariant event. Previous studies suggested that some resident organisms, including freshwater fishes, birds and frogs, may have been pushed into upland areas by elevated salinity in lowland regions [11,41,42]. Such situations would have isolated populations and over time led to allopatric speciation [1].…”
Section: Discussionmentioning
confidence: 99%